Geology, zircon geochronology, and petrogenesis of Sabalan volcano (northwestern Iran) - Ghalamghash, Jalil; Mousavi, S. Z.; Hassanzadeh, Judith Parwane; Schmitt, A. K. (Journal of volcanology and geothermal research, 2016)
Sabalan Volcano (NW Iran) is an isolated voluminous (4821m elevation; >800km2) composite volcano that is located within the Arabia-Eurasia collision zone. Its edifice was assembled by recurrent eruptions of trachyandesite and dacite magma falling into a relatively restricted compositional range (56-67% SiO2) with high-K calc-alkaline and adakitic trace element (Sr/Y) signatures. Previous K-Ar dating suggested protracted eruptive activity between 5.6 and 1.4Ma, and a two stage evolution which resulted in the construction of the Paleo- and Neo-Sabalan edifices, respectively. The presence of a topographic moat surrounding Neo-Sabalan and volcanic breccias with locally intense hydrothermal alteration are indicative of intermittent caldera collapse of the central part of Paleo-Sabalan. Volcanic debris-flow and debris-avalanche deposits indicate earlier episodes of volcanic edifice collapse during the Paleo-Sabalan stage. In the Neo-Sabalan stage, three dacitic domes extruded to form the summits of Sabalan (Soltan, Heram, and Kasra). Ignimbrites and minor pumice fall-out deposits are exposed in strongly dissected drainages that in part have breached the caldera depression. Lavas and pyroclastic rocks are varyingly porphyritic with Paleo-Sabalan rocks being trachyandesites carrying abundant phenocrysts (plagioclase+amphibole+pyroxene+biotite). The Neo-Sabalan rocks are slightly more evolved and include dacitic compositions with phenocrysts of plagioclase+amphibole±alkali-feldspar±quartz. All Sabalan rock types share a common accessory assemblage (oxides+apatite+zircon). High spatial resolution and sensitivity U-Pb geochronology using Secondary Ionization Mass Spectrometry yielded two clusters of zircon ages which range from 4.5 to 1.3Ma and 545 to 149ka, respectively (all ages are averages of multiple determinations per sample). U-Th zircon geochronology for selected Neo-Sabalan rocks agrees with the U-Pb ages, with the youngest zircon rims dating to ca. 110 ka. Because zircon crystallization predates eruption, this age represents the upper limit for the youngest eruptions of Sabalan. Valley-filling ignimbrites yielded variable U-Pb zircon ages which argue against these pyroclastic rocks being generated in a single caldera forming event. These results indicate that eruptions occurred more recently than previously indicated by K-Ar dating. Paleo-Sabalan and Neo-Sabalan volcanic rocks have similar geochemical characteristics, including enrichment of LILE and LREE relative to HFSE and HREE, respectively, and prominent negative Ti, Nb, and Ta anomalies. The trachyandesitic to dacitic rocks of Sabalan also share negative Eu anomalies. This, together with horizontal or slightly increasing Y vs. Rb trends, indicates fractionation of plagioclase-amphibole or plagioclase-clinopyroxene assemblages with negligible crustal assimilation (based on low and invariant Rb/Th). High degrees of mantle partial melting are inferred from high (La/Yb)N (from 28 to 48). Overall, the subduction-affinity of Sabalan volcanic rocks agrees with models of melt generation following a Quaternary slab break-off event coeval with continental collision.
Gesehen am 05.06.2020